Studies on the epipolythiodioxopiperazine alkaloid verticillin D: Scaled production, streamlined purification, and absolute configuration - Herma C. Pierre; Devyani J. Patel; Huzefa A. Raja; Blaise A. Darveaux; Krupa I. Patel; Lina Mardiana; Alexandra Longcake; Michael J. Hall; Michael R. Probert; Cedric J. Pearce; Nicholas H. Oberlies (Phytochemistry, 2025)

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Production of 17- O -demethyl-geldanamycin, a cytotoxic ansamycin polyketide, by Streptomyces hygroscopicus DEM20745 - Aron Baksh; Bernhard Kepplinger; Hadiza A. Isah; Michael R. Probert; William Clegg; Corinne Wills; Michael Goodfellow; Jeff Errington; Nick Allenby; Michael J. Hall (Natural Product Research, 2017)

A continental-scale study of seed lifespan in experimental storage examining seed, plant, and environmental traits associated with longevity - David J. Merritt; Amelia J. Martyn; Phillip Ainsley; Renee E. Young; Leahwyn U. Seed; Michael Thorpe; Fiona R. Hay; Lucy E. Commander; Nancy Shackelford; Catherine A. Offord; Kingsley W. Dixon; Robin J. Probert (Biodiversity and Conservation, 2014)

Conservation Planning with Multiple Organizations and Objectives - MICHAEL BODE; WILL PROBERT; WILL R. TURNER; KERRIE A. WILSON; OSCAR VENTER (Conservation Biology, 2011)
There has been a dramatic increase in the number of conservation organizations worldwide. It is now common for multiple organizations to operate in the same landscape in pursuit of different conservation goals. New objectives, such as maintenance of ecosystem services, will attract additional funding and new organizations to conservation. Systematic conservation planning helps in the design of spatially explicit management actions that optimally conserve multiple landscape features (e.g., species, ecosystems, or ecosystem services). But the methods used in its application implicitly assume that a single actor implements the optimal plan. We investigated how organizational behavior and conservation outcomes are affected by the presence of autonomous implementing organizations with different objectives. We used simulation models and game theory to explore how alternative behaviors (e.g., organizations acting independently or explicitly cooperating) affected an organization's ability to protect their feature of interest, and investigated how the distribution of features in the landscape influenced organizations’ attitudes toward cooperation. Features with highly correlated spatial distributions, although typically considered an opportunity for mutually beneficial conservation planning, can lead to organizational interactions that result in lower levels of protection. These detrimental outcomes can be avoided by organizations that cooperate when acquiring land. Nevertheless, for cooperative purchases to benefit both organizations’ objectives, each must forgo the protection of land parcels that they would consider to be of high conservation value. Transaction costs incurred during cooperation and the sources of conservation funding could facilitate or hinder cooperative behavior.